Classroom Assessment as Co-Regulated Learning: A Systematic Review - Andrade, Heidi L.; Brookhart, Susan M.; Yu, Elie ChingYen (Frontiers in Education, 2021)
Current conceptions of assessment describe interactive, reciprocal processes of co-regulation of learning from multiple sources, including students, their teachers and peers, and technological tools. In this systematic review, we examine the research literature for support for the view of classroom assessment as a mechanism of the co-regulation of learning and motivation. Using an expanded framework of self-regulated learning to categorize 94 studies, we observe that there is support for most but not all elements of the framework but little research that represents the reciprocal nature of co-regulation. We highlight studies that enable students and teachers to use assessment to scaffold co-regulation. Concluding that the contemporary perspective on assessment as the co-regulation of learning is a useful development, we consider future directions for research that can address the limitations of the collection reviewed.